Efficacy of a multi-nutrient dietary supplement on improving decision fatigue in video gamers - Seesurn, Bandana; Batllori, Rodrigo; Watson, Shawn N. (Frontiers in Nutrition, 2025)
IntroductionGamers can experience decision fatigue, affecting decision-making and overall performance. This pilot study evaluated a multi-nutrient supplement called Numin on decision fatigue, video game performance, cognitive function, and mouse and keyboard input mechanics assessed as physical aspects of video gamers. Formulated with active ingredients like Methylsulfonylmethane, L-Tyrosine, Rhodiolife®, TurmiPure Gold®, and Chromium Picolinate, Numin was examined in a randomized, placebo-controlled, crossover study.MethodsHealthy adults with at least “Silver” skill rating were enrolled from February 6 to 13, 2022 in Arizona, USA. Participants played 10 competitive games of League of Legends (LoL). The primary endpoint was the change in decision fatigue between study groups, measured using Decision Fatigue Scale (DFS) and video game performance.ResultsDFS scores were lower in the intervention group than in the placebo group, while cognitive assessment scores were higher in the intervention group for most tasks compared to the placebo group. However, these differences were not significant. Video game performance significantly improved in the intervention group regarding average deaths when losing, gold spent percentage difference, and perhaps most importantly, win rates compared to the placebo group (p < 0.05 for all). While the intervention group showed no significant difference in chat cycles or champion recall, the placebo group demonstrated significant reductions in both, indicating that the intervention group maintained performance in these aspects relative to the decline in the placebo group. The intervention group showed significant changes in the number of mouse clicks and mouse movements, compared to the placebo group.DiscussionNumin is hypothesized to exert neuroprotective effects by improving glutamate re-uptake and protecting against excitotoxic injury, thereby supporting neuronal health and neurotransmission. While direct measures of decision fatigue and cognition did not show statistically significant improvements, these mechanisms may contribute to the observed enhancements in gaming performance and win rates by mitigating the molecular and cellular events underlying cognitive decline under prolonged demands. Our findings indicate that Numin improved video game performance in LoL gamers, suggesting it may support cognitive function during intense tasks. This study highlights the potential application and benefits of such a supplement in individuals undergoing cognitively intense tasks, such as gaming.